Corporate Social Responsibility Failures: How do Consumers Respond to Corporate Violations of Implied Social Contracts? - Russell, Cristel Antonia (Journal of business ethics, 2016)
This research documents consumers’ potential to monitor corporations’ License to Operate through their consumption responses to corporate social responsibility failures. The premise is that the type of social contracts or standards in place may determine how consumers, through their individual and collective behaviors, can play a direct role in influencing corporate behavior, when corporations fail to meet social responsibility standards. An experiment conducted with a large sample of consumers in the United States shows that consumers respond differently to a company’s failure in its social responsibilities depending on whether the violated standard is a government mandate or a voluntary commitment and depending on the consumers’ own environmental consciousness. The findings highlight the potential power of individual consumers and consumer collectives in narrowing the governance gaps relative to social and environmental issues and reducing the likelihood of CSR failures.